Arbuscular Mycorrhizas: Physiology and Function 2000
DOI: 10.1007/978-94-017-0776-3_11
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of arbuscular mycorrhizal fungi with other soil organisms

Abstract: Abstract:futeractions between arbuscular mycorrhizal (AM) fungi and other soil microorganisms (including bacteria, saprophytic microfungi, actinomycetes and some microarthropods) are described as well as the phenomena of the rhizosphere, mycorrhizosphere and mycosphere. Examples are given of how the growth of AM fungi and the formation of mycorrhizas are affected by the other soil organisms. All of these co-occuring positive and negative influences upon the interaction between AM fungi and plant roots are show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 99 publications
1
44
1
Order By: Relevance
“…Generally, AM fungi are known to favour the growth of benefi cial microbes and both AM fungi and other microbes are known to infl uence each other [21,22]. In the present study, contrasting results were obtained for AM fungi and other microbial population.…”
Section: Discussioncontrasting
confidence: 64%
“…Generally, AM fungi are known to favour the growth of benefi cial microbes and both AM fungi and other microbes are known to infl uence each other [21,22]. In the present study, contrasting results were obtained for AM fungi and other microbial population.…”
Section: Discussioncontrasting
confidence: 64%
“…For example, Klironomos and Moutoglis (1999) showed that the collembola Folsomia candida increased the dispersal range of Glomus etunicatum by at least 30 cm. On the other hand, AM fungi can also be vectors for other soil organisms (Gryndler 2000). For example, Bianciotto et al (1996) found that several strains of rhizobia and pseudomonads adhere to the surface of AM fungal spores, hyphae, and auxiliary cells and thus, AM fungi may transport these soil microbes throughout the soil.…”
Section: Dispersal or Destruction Of Propagulesmentioning
confidence: 98%
“…A recent review (Gryndler 2000) illustrates the diversity of interactions between AM fungi and other soil organisms involving both stimulatory and inhibitory compounds. For example, an isolate of Aspergillus niger that produced substances similar to indole-3-acetic acid and gibberellic acid was shown to increase the fitness of both Glomus fasciculatum and the host plant (Manjunath et al 1981).…”
Section: Stimulatory or Inhibitory Compoundsmentioning
confidence: 99%
“…Rhizobium spp. may act synergistically with arbuscular mycorrhizal (AM) fungi on their plant hosts (Gryndler 2000) (Fig. 18.1).…”
Section: What Is Rhizosphere/mycorhizosphere?mentioning
confidence: 99%